KARAKTERISTIK POLA PEMAKAIAN DAN PELAYANAN AIR BERSIH DI WILAYAH USAHA PAM PT. TIRTAARTHA BUANAMULIA - Suryadmaja, I B.; Norken, I N.; Sila Dharma, I G.B. (JURNAL SPEKTRAN; Vol. 3, No. 1, Januari 2015DO - 10.24843/SPEKTRAN.2015.v03.i01.p03)
A bstract : The purpose of this study is to determine how the pattern of usage, behavior and water services in the areas of business of  PAM PT.Tirtaartha Buanamulia (PT.TB) using qualitative descriptive methods such as survey research instrument (observation) and questionnaires of 337 samples, consisting of domestic water consumption and non- domestic . The result of the analysis showed that the average water consumption in some parts of sub-district of Kuta (Kedonganan village, Tuban village and Kuta village), the business area of PAM PT. TB, amounts to 243.49 liters /person /day. Average water use in the District of South Kuta (Pecatu village, Ungasan village, Kutuh village, Benoa vilage, Tanjung Benoa village and Jimbaran village) amounts 168.01 liters/person/day. Calculation of water demand for star hotels based on the results of the study on average is 726.84 liters /room/ day and non-star hotels 43.85 liters/room/day, the need of water for the restaurant and the restaurant is based on the research of 18.85 liters/seat/day, water usage for educational facilities based on the results of the study amounted to 9.99 liters/person/day, the water requirements for health facilities based on the research needs 562.13 liters /bed/day. The amount of non- domestic water needs based on research results which was 72.69 % of the domestic water needs, is the basis for the provision of water by PAM PT. TB at this time and in the future. The analysis of the results showed that the community of water users in the area of business PAM PAM PT. TB had a good perception of the PAM service; this is evidenced by the level of customer satisfaction to achieve 73.07 % PAM services for domestic and non- domestic 100 %. This study also showed the willingness of subscribers received 10 % increase in the tariff.
Keywords: services, domestic water, and non- domestic , customer satisfaction